ABIOTIC AND BIOTIC POTENTIAL IN THE DEVELOPMENT OF RURAL-BASED ECOTOURISM: A STUDY ON BANTAR KULON VILLAGE, LEBAKBARANG DISTRICT, PEKALONGAN REGENCY, INDONESIA - Halim Ahmad; Tri Retnaningsih Soeprobowati; Hartuti Purnaweni; Faiq Rahman (Universitas Trisakti, 2025)
Aim: This study aims to identify the diversity of biotic, abiotic and culture in Bantar Kulon Village. Methodology and Result: This study uses a combination of qualitative and quantitative research approaches, using descriptive research techniques and ROS (Recreation Opportunity Spectrum). Bantar Kulon Village has a diversity of 5 abiotic potentials in the form of geographical and geological conditions, biotic potentials in 43 types of flora and 48 types of fauna, including 1 species has the status of Not Evaluated; (NE), 8 species have a Data Deficient status (DD), 43 species with Least Concern status (LC), 3 species with Near Threatened status (NT), 3 species Vulnerable (VU), 6 species have Endangered status (EN) and 1 species with Critically Endangered status (CR) based on the status of the International Union for Conservation of Nature (IUCN) Red List, also 13 cultural potentials in the form of art, traditions, sites, and local wisdom. Conclusion, Significance and Impact Study: The potential of abiotic and biotic, also cultural elements of Bantar Kulon Village are very valuable to be capitalized in the form of ecotourism activities. The aspirations of tourists are in Class IV, while the perception of the community towards the development of ecotourism in Bantar Kulon Village is in Class III. This study suggests that limited adjustments should be made, especially in the fulfillment of accessibility and facilities so that the development of tourism in Bantar Kulon Village is more in line with tourist aspirations.